Pakistan : Second Review Under the Extended Arrangement and Request for Waivers of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper assesses Pakistan's Second Review Under the Extended Arrangement and Request for Waivers of Non-Observance of Performance Criteria. Discussions focused on progress in addressing the main macroeconomic challenges facing the country and remedial actions to meet missed performance criteria. Pakistan's economic growth is expected to remain modest with GDP growth forecast revised upward to 3.1 percent. The IMF report highlights that the preliminary data for the first quarter of FY13/14 showed 5 percent growth, mainly driven by services and manufacturing.